2004
DOI: 10.1258/002221504772784504
|View full text |Cite
|
Sign up to set email alerts
|

Air-conditioning characteristics of the human nose

Abstract: Nasal inspiration is important for maintaining the internal milieu of the lung, since ambient air is conditioned to nearly alveolar conditions (body temperature and fully saturated with water vapour) upon reaching the nasopharynx. This literature review of the existing in vivo, in vitro and computational studies on transport phenomena that take place within the human nasal cavity summarizes the current knowledge on air-conditioning characteristics of the human nose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 34 publications
2
60
0
3
Order By: Relevance
“…In addition, the same authors found that a high increase of humidity and temperature was found in the anterior nasal segment and that further increase of both parameters between the turbinate area and nasopharynx was less pronounced in spite of the longer distance (Keck et al, 2000a). A review paper by Wolf et al (2004) also discussed the air-conditioning characteristics of the human nose through results of in-vivo, in-vitro and computational simulations. It is noted that the computational simulations were based on simplified models of the nasal cavity.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the same authors found that a high increase of humidity and temperature was found in the anterior nasal segment and that further increase of both parameters between the turbinate area and nasopharynx was less pronounced in spite of the longer distance (Keck et al, 2000a). A review paper by Wolf et al (2004) also discussed the air-conditioning characteristics of the human nose through results of in-vivo, in-vitro and computational simulations. It is noted that the computational simulations were based on simplified models of the nasal cavity.…”
Section: Introductionmentioning
confidence: 97%
“…Though each task separately constitutes a difficult challenge, the nose attains a remarkable level of performance in all three. Firstly, inspired air largely attains body temperature and saturation before reaching the glottis (Mygind & Dahl 1998;Wolf et al 2004). Secondly, although olfactory sensitivity depends on a host of factors, including the particular odorant molecule, threshold values for olfactory detection in the low tens of parts per billion have been reported (Walker et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The nasal cavity serves three principal roles: (i) it warms and humidifies inspired air, (ii) it protects and defends the lower respiratory tract by filtering particles and trapping some pathogens, and (iii) it houses the olfactory receptors [2,3]. Filtration of particles involves deposition on the cavity walls or on the nasopharynx with nearly all particles greater than 5µm and about 50% of those 2 − 4µm captured while the majority of particles smaller than 2µm bypass the nose [2].…”
Section: Introductionmentioning
confidence: 99%
“…The nasal cavity serves three principal roles: (i) it warms and humidifies inspired air, (ii) it protects and defends the lower respiratory tract by filtering particles and trapping some pathogens, and (iii) it houses the olfactory receptors [2,3]. Filtration of particles involves deposition on the cavity walls or on the nasopharynx with nearly all particles greater than 5µm and about 50% of those 2 − 4µm captured while the majority of particles smaller than 2µm bypass the nose [2]. Air-conditioning involves both heating and humidifying the air on inspiration (23 o C, 40% relative humidity at the nares to 33 o C, 98% relative humidity) while recapturing some heat and humidity on expiration (37 o C, 98% relative humidity to 33 o C, 85% relative humidity at the nares, resulting in ∼ 100ml of water per day being saved) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation